2017
DOI: 10.1002/anie.201609792
|View full text |Cite
|
Sign up to set email alerts
|

Individual (f,tA)‐ and (f,tC)‐Fullerene‐Based Nickel(II) Glycinates: Protected Chiral Amino Acids Directly Linked to a Chiral π‐Electron System

Abstract: Stereoselective electrosynthesis of the first individual ( A)- and ( C)-1,4-fullerene derivatives with a non-inherently chiral functionalization pattern is described, as well as the first example of an optically pure protected primary amino acid directly linked to the fullerene through only the chiral α-amino-acid carbon atom. An application of an auxiliary chiral nickel-Schiff base moiety as derivatizing agent allowed separation of ( A)- and ( C)-1,4-fullerene derivatives using an achiral stationary phase, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Various types of reactions are compatible with this methodological platform, as represented by alkyl halide alkylations; Michael, Mannich, and aldol addition reactions; as well as multistep transformations, affording a wide range of practically important α‐ and β‐amino acids . Recently, asymmetric synthesis via metal Schiff base complexes was combined with the electrochemical activation approach, which disclosed a virtually unexplored methodological facet of this area of research.…”
Section: Introductionmentioning
confidence: 99%
“…Various types of reactions are compatible with this methodological platform, as represented by alkyl halide alkylations; Michael, Mannich, and aldol addition reactions; as well as multistep transformations, affording a wide range of practically important α‐ and β‐amino acids . Recently, asymmetric synthesis via metal Schiff base complexes was combined with the electrochemical activation approach, which disclosed a virtually unexplored methodological facet of this area of research.…”
Section: Introductionmentioning
confidence: 99%
“…Elaboration of new stereoselective synthetic approaches to organic molecules is a topical problem nowadays since the configuration of stereocenters often determines properties of diastereomers and possibilities for their practical applications . Recently, we started an extensive research on the application of electrochemical activation in stereoselective synthesis in a coordination environment of chiral metal complexes . Wide capabilities provided by electrochemical techniques open new horizons in stereoselective synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…New compounds which were not available using common approaches were obtained when cathodic or anodic activation of the starting compounds was applied . The other possible approach – deprotonation with electrochemically generated base – provides the possibility of a precise control on the concentration of a base and its in situ reaction with the complex, thus opening up the possibility of carrying out multistep stereoselective one‐pot transformations . Here we report a new electrochemical route for the stereoselective oxyalkylation of glycine in a Ni II coordination environment (Scheme ) using in situ electrogenerated active species.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical deprotonation of (S)-2 was performed with azobenzene radical-anions (at the potential of their formation, −1.32 V vs. Ag/AgCl/KCl). After complete deprotonation of (S)-2, C60 was added to Magdesieva and co-authors [75] reported the first example of regio-and stereoselective electrosynthesis of the protected primary fulleroamino acid with double chirality (Scheme 28). Compounds (77a and 77b) have three chiral centers in the addend (including the stereogenic α-amino-acid carbon center directly bound to the fullerene) and the fullerene cage itself exhibits a non-inherently chiral 1,4-functionalization pattern.…”
Section: Scheme 25 Asymmetric 16-conjugate Addition Reaction Of Ni(mentioning
confidence: 99%
“…Magdesieva and co-authors [ 75 ] reported the first example of regio- and stereoselective electrosynthesis of the protected primary fulleroamino acid with double chirality ( Scheme 28 ). Compounds ( 77a and 77b ) have three chiral centers in the addend (including the stereogenic α-amino-acid carbon center directly bound to the fullerene) and the fullerene cage itself exhibits a non-inherently chiral 1,4-functionalization pattern.…”
Section: Addition Reactionsmentioning
confidence: 99%